THE ASSISTANCE OF PREGNANCY CLASS TO INCREASE KNOWLEDGE OF PREGNANT WOMEN - Sri Untari; Rizki Sahara; Nur Fatimah; Nurul Kodiyah; Dhiyan Nany Wigati; Meity Mulya Susanti; Riska Indriyati; Nada Silmia Millati (LPPM AN Nuur, 2024)
Background : Pregnancy class is a study group who has a purpose to transfer knowledge about comprehensive health of pregnancy, that includes how to take care of pregnancy, delivery, post partum and neonates, myth, trust, tradition, sexual transmited disease and birth certificate. the purpose of pregnancy class is make pregnant woman and their husband to improve knowledge, changing attitudes and behaviours about pregnancy, delivery. Post partum and neonatal care. Methodology : transfer knowledge with give an explanation, question and answer section, brainstorming, material are provided with book who give for pregnant woman, leaflet. Result : health education at pregnancy class can be improve about knowledge of pregnant women. The materials presented included danger signs in early moments of pregnancy, signs of delivery, maternity care, postpartum care, psychological changes in postpartum and neonatal care.Conclusion : pregnancy class will improve significant knowledge of pregnant woman.